Midwifery Care In The Pollution Period With Level II Perineal Rupture Pain At The Palangga Health Center - Aji, Sulistyani Prabu; Rosita, Rosita; Saide, Rusnaeni; Sabriana, Riska; Lubis, Halimatussakdiyah; Fatimah, Sitti; Alfah, Siti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
A perineal wound is a condition where tissue continuity is broken which occurs in almost all first deliveries and not infrequently also occurs in subsequent deliveries. If this situation is not handled properly, bleeding infection can occur which can result in high maternal morbidity and mortality. The aim of the research is to carry out Midwifery Care for the Postpartum Period with Level II Perineal Rupture using a midwifery management approach in accordance with the midwife's authority. The research method used is the case study writing method, namely carrying out case studies using a midwifery management approach. Results of a study on the implementation and implementation of midwifery care for clients with Grade II Perineal Rupture Pain at the Palangga Community Health Center, Gowa Regency. In the theoretical application of midwifery care, starting from data analysis, formulating actual and potential future diagnoses. Immediate action or collaboration, planning, management and evaluation of midwifery care that occurs.